ANALISIS KINERJA BIAYA DENGAN METODE NILAI HASIL (EARNED VALUE ANALYSIS) PADA PEKERJAAN PEMBANGUNAN AULA LEMBAGA PENJAMIN MUTU PENDIDIKAN SAMARINDA KALIMANTAN TIMUR - SONDAKH, MIRYAM ANGGERENI (KURVA S JURNAL MAHASISWA, 2020)
: In the implementation of a network construction project it is rare to find a project that is exactly as planned. Hall construction work is an effort carried out in development with the aim of gaining a return on investment, therefore an integrated cost analysis is needed to avoid losses that can be controlled by the project in terms of cost by the Earned Value method. in this study is the construction of the Hall of the Education Quality Assurance Institute (LPMP) on Cipto Mangunkusumo KM.2 Samarinda Seberang, East Kalimantan as a research location, in this study the cost of building the Hall will be evaluated During the project implementation there are many obstacles that may occur that cause the project to experience a loss in costs, not in accordance with the planned or delayed work, A method is needed that aims to control these constraints during project implementation in order to avoid losses in the development activities. Using the Earned Value Analysis method, in the Hall of Education Quality Assurance Institution building project on Cipto Mangunkusumo KM.2 Samarinda, Seber- ang, East Kalimantan as the research location. This research was conducted to control project costs in an integrated manner with the Earned Value method so that it can know the performance of the activities being carried out and can increase effectiveness in increasing project activities in order to obtain maximum results from available resources. Can be concluded the results of the cost calculation using the earned value analysis method in the LPMP Hall construction. In this study Time and Cost Performance Analysis with Value Earned Analysis Method in Mulawarman Residence Samarinda Housing Development resulted in the value of SPI 0.907 while the CPI was 1,024, From the results of the calculation of the costs for the remaining work (ETC) the results obtained are Rp. 350,486,693.22, and for the estimated total cost of the project with the estimated total cost of the project (EAC) the results were 3,078,214,349,52